2009
DOI: 10.1111/j.1865-1682.2009.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antigenic Cross-Reactivity Between Subgroup C Avian Pneumovirus and Human Metapneumovirus by Using Recombinant Fusion Proteins

Abstract: Avian pneumovirus subgroup C (APV/C) has recently been reported to be more closely related to human metapneumovirus (hMPV) as determined by sequence analysis. To examine the antigenic relationship between APV/C and hMPV, the APV/C fusion (F) gene was cloned and expressed as an uncleaved glycoprotein in a baculovirus system. The reactivity of the APV/C F protein with antibodies against APV subgroups A, B, C, and hMPV was examined by Western blot analysis. The results showed that the expressed APV/C F protein wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The fixed cells were then incubated with a monoclonal antibody (MAB80123, Temecula, MILLIPORE) against the F protein of hMPV as described by Luo et al [10].…”
Section: Indirect Immunofluorescence Assay (Ifa)mentioning
confidence: 99%
See 2 more Smart Citations
“…The fixed cells were then incubated with a monoclonal antibody (MAB80123, Temecula, MILLIPORE) against the F protein of hMPV as described by Luo et al [10].…”
Section: Indirect Immunofluorescence Assay (Ifa)mentioning
confidence: 99%
“…When CPE was evident, the cells infected or mock-infected with S-01 or S-01/ anti-serum were detected by IFA, as described by Luo et al [10].…”
Section: Neutralization Testmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no antibody available for the subgroup C aMPV, but our amino acid sequencing revealed that the F protein of S-01 was identical to that of aMPV-C and hMPV by 98.5-99.1% and 81.6-81.8%, respectively. Because Luo et al used recombinant fusion protein [10] to confirm that there was high antigenic cross-reactivity between aMPV-C and hMPV, we used an antibody against the F protein of hMPV for the immunofluorescence assay. The results show that the antigen of S-01 could effectively bind to the antibody in Vero cells (Figure 3D), whereas no fluorescence was observed in mock-infected Vero cells (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…aMPV was first reported in South Africa in 1980 [3], was subsequently reported in France [4] and the United Kingdom [5] and was recently described worldwide [6]–[9]. Based on the antigenicity and genetic characterization, aMPV was further categorized into four subtypes, designated A, B, C and D [10],[11]. aMPV is an enveloped, single-stranded, negative-sense RNA virus.…”
Section: Introductionmentioning
confidence: 99%